Assessment of pain levels in patients undergoing foot surgery - de Albuquerque, Gabriel Souza; Teixeira, Marcelo de Brito; Juste, Miguel Lanzieri; Melo, Daniel Gomes de Aguiar; Alves, Lucas Jorge Santana de Castro; Moreno, Marcus Vinicius Mota Garcia (Scientific Journal of the Foot & Ankle, 2018)
Objective: To analyze the use of an anesthetic ankle block in the immediate postoperative period in patients undergoing foot surgery to evaluate the quality of postoperative recovery and in-hospital opioid use. Methods: Presentation of the preliminary results of a randomized, placebo-controlled, double-blind trial conducted from May 2016 to January 2017, with 16 patients undergoing surgery to correct foot pathologies. The patients in the intervention group were treated with an additional ankle block and compared to a control group. Results: The intervention group included eleven patients, of whom ten had mild pain, with a mean visual analog pain scale (VAS) score of 3 and a mean quality of post-surgical recovery (QoR-40) of 194; none of these patients required the use of opioids. The control group included five patients. Of these, one patient had severe pain and two showed moderate pain. The mean VAS score in this group was 4, and the mean QoR-40 was 190. Three patients from this group required opioids. Conclusion: The use of an ankle block in the 24 h immediately post-surgery reduced pain scores and the need for opioid use and improved postoperative recovery. Level of Evidence I; Therapeutic Studies; Randomized Clinical Study.